Infection‐related and ‐unrelated malignancies, HIV and the aging population. Issue 8 (18th February 2016) - Shepherd, L; Borges, ÁH; Ledergerber, B; Domingo, P; Castagna, A; Rockstroh, J; Knysz, B; Tomazic, J; Karpov, I; Kirk, O; Lundgren, J; Mocroft, A; et al.
Abstract : Objectives: HIV‐positive people have increased risk of infection‐related malignancies (IRMs) and infection‐unrelated malignancies (IURMs). The aim of the study was to determine the impact of aging on future IRM and IURM incidence. Methods: People enrolled in EuroSIDA and followed from the latest of the first visit or 1 January 2001 until the last visit or death were included in the study. Poisson regression was used to investigate the impact of aging on the incidence of IRMs and IURMs, adjusting for demographic, clinical and laboratory confounders. Linear exponential smoothing models forecasted future incidence. Results: A total of 15 648 people contributed 95 033 person‐years of follow‐up, of whom 610 developed 643 malignancies [IRMs: 388 (60%); IURMs: 255 (40%)]. After adjustment, a higher IRM incidence was associated with a lower CD4 count [adjusted incidence rate ratio (aIRR) CD4 count < 200 cells/μL: 3.77; 95% confidence interval (CI) 2.59, 5.51; compared with ≥ 500 cells/μL], independent of age, while a CD4 count < 200 cells/μL was associated with IURMs in people aged < 50 years only (aIRR: 2.51; 95% CI 1.40–4.54). Smoking was associated with IURMs (aIRR: 1.75; 95% CI 1.23, 2.49) compared with never smokers in people aged ≥ 50 years only, and not with IRMs. The incidences of both IURMs and IRMs increased with older age. It was projected that the incidence of IRMs would decrease by 29% over a 5‐year period from 3.1 (95% CI 1.5–5.9) per 1000 person‐years in 2011, whereas the IURM incidence would increase by 44% from 4.1 (95% CI 2.2–7.2) per 1000 person‐years over the same period. Conclusions: Demographic and HIV‐related risk factors for IURMs (aging and smoking) and IRMs (immunodeficiency and ongoing viral replication) differ markedly and the contribution from IURMs relative to IRMs will continue to increase as a result of aging of the HIV‐infected population, high smoking and lung cancer prevalence and a low prevalence of untreated HIV infection. These findings suggest the need for targeted preventive measures and evaluation of the cost−benefit of screening for IURMs in HIV‐infected populations.